Bioethics, environmental ethics, promoting life towards a sustainable human and environmental existence - Gianan, Nicolito A. (Asia Life Sciences : the Asian International Journal of Life Sciences, 2008)
Promoting a healthy human life irrefutably hinges on a healthy environment and on the human community's capability not just to conserve but also to sustain the positive interaction between human-induced activities and the environment. And considering the existence and ethical disposition of the human in dealing with environmental health would be significantly important for upholding life, since the human is primarily and actively involved in it. Thus, because of intelligence and will, this involvement imposes the ultimate responsibility and accountability on the human in promoting life. The possession of ultimate responsibility and accountability reveals the human's life ethics, also known as bioethics. Bioethics encompasses other ethical fields and most important in it is the human's positive relation and interaction with the environment or the co-called environmental ethics. Nevertheless, no other being but the human has the intelligence to solve the apparent environmental problems and the will to prevent further problems, particularly those induced by fellow humans. The human, therefore, can and will make decisions for promoting life, neither the irrational animals nor plants. The human actualizes these decisions not only for the human community but also for the environment including all its mechanisms, towards living a healthy life (above all healthy human life - the central theme of bioethics and environmental ethics) and its existential sustainability in a healthy environment.